Change the world : how ordinary people can achieve extraordinary results - Quinn, Robert E. (San Francisco : Jossey Bass Publishers, 2000)
"Change the World presents eight principles that each of us can follow to make individual and organizational change happen: envision the productive community; first look within; embrace the hypocritical self; transcend fear; embody a vision of the common good; disturb the system; surrender to the emergent process; and entice through moral power. These are principles inspired by the teachings of Jesus, Gandhi, and Martin Luther King, Jr. - three historical leaders who successfully used personal change to change the world."--Jacket.
1. An Invitation to Transformation -- 2. Envision the Productive Community -- 3. First Look Within -- 4. Embrace the Hypocritical Self -- 5. Transcend Fear -- 6. Embody a Vision of the Common Good -- 7. Disturb the System -- 8. Surrender to the Emergent Process -- 9. Entice Through Moral Power -- App. A. A Summary of Advanced Change Theory -- App. B. Some Criticisms of ACT.
Includes bibliographical references (pages 257-260) and index.
Keywords: Organizational change; Social change; Change (Psychology)